2021
DOI: 10.4103/jcd.jcd_636_20
|View full text |Cite
|
Sign up to set email alerts
|

To compare the continuous and intermittent irrigation method on the removal of dentin debris from root canals and to evaluate the dynamics of irrigant flow using computational fluid dynamics

Abstract: Aim: This study aimed to compare the efficiency of continuous and intermittent irrigating methods on the removal of dentin debris from the simulated grooves and to evaluate the dynamics of irrigant using computational fluid dynamics (CFD). Methodology: Seventy-five extracted human permanent maxillary canines were selected. Access cavities were made, working length was determined, and canals were prepared by crown down technique. The teeth were split longitudinally and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, ultrasonic irrigation can be used in two different methods, one was continuous irrigation with irrigant delivering into the root canal continuously, and the other was intermittent irrigation with the discontinuous flow but the same cumulative irrigation time. Raj et al 46 reported that continuous irrigation had a better effect on the removal of debris in simulated grooves than intermittent irrigation. It was because continuous irrigation helped in the continuous activation of the irrigant and thus led to better debridement of the root canal.…”
Section: Recent Cfd Analysis Of Root Canal Irrigationmentioning
confidence: 99%
“…In addition, ultrasonic irrigation can be used in two different methods, one was continuous irrigation with irrigant delivering into the root canal continuously, and the other was intermittent irrigation with the discontinuous flow but the same cumulative irrigation time. Raj et al 46 reported that continuous irrigation had a better effect on the removal of debris in simulated grooves than intermittent irrigation. It was because continuous irrigation helped in the continuous activation of the irrigant and thus led to better debridement of the root canal.…”
Section: Recent Cfd Analysis Of Root Canal Irrigationmentioning
confidence: 99%
“…Therefore, irrigation is essential to remove debris and to obtain disinfected root canal system, although there are new methods for root canal irrigation, such as sonic or ultrasonic activation, the conventional root canal irrigation method still has common use among dentists for root canal treatment [9]. Effectiveness and the safety of the root canal irrigation depends on several factors and various methods have been proposed to test these parameters in the last decade ( [10], [11], [12], [13], [14] and [15]), however these methods provided insufficient insight into the irrigation process [16]. Computational Fluid Dynamics (CFD) is finite-volume based numerical solution technique for fluid dynamics problems [17].…”
Section: Introductionmentioning
confidence: 99%
“…Computational Fluid Dynamics (CFD) is finite-volume based numerical solution technique for fluid dynamics problems [17]. CFD is a powerful method to evaluate flow characteristics by means of streamlines, velocity distributions, shear stresses and pressure on the root canal wall, that are difficult to measure in vivo due to the complex anatomy of the root canal [16]. CFD can be considered as a promising tool to investigate the effect of needle tip design on root canal irrigation and potential irrigant extrusion risks, as in many engineering problems.…”
Section: Introductionmentioning
confidence: 99%